2013
DOI: 10.4161/tisb.24333
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-4 and interleukin-13 cause barrier dysfunction in human airway epithelial cells

Abstract: Emerging evidence indicates that airway epithelial barrier function is compromised in asthma, a disease characterized by Th2-skewed immune response against inhaled allergens, but the mechanisms involved are not well understood. The purpose of this study was to investigate the effects of Th2-type cytokines on airway epithelial barrier function. 16HBE14o- human bronchial epithelial cells monolayers were grown on collagen coated Transwell inserts. The basolateral or apical surfaces of airway epithelia were expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
117
3
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(138 citation statements)
references
References 21 publications
10
117
3
3
Order By: Relevance
“…Rather, these investigators found that TNF-α causes marked AJC disassembly in a Src-dependent manner. We found that both IL-4 and IL-13 induced barrier disruption in 16HBElo- cells by inhibiting surface expression of ZO-1, occludin, E-cadherin and β-catenin 20 . In contrast to the Th2-depdendent induction of leaky claudin-2 observed in intestinal epithelia, neither IL-4 nor IL-13 induced claudin-2 expression in 16HBElo- cells.…”
Section: Models Of Inducible Barrier Dysfunctionmentioning
confidence: 74%
See 1 more Smart Citation
“…Rather, these investigators found that TNF-α causes marked AJC disassembly in a Src-dependent manner. We found that both IL-4 and IL-13 induced barrier disruption in 16HBElo- cells by inhibiting surface expression of ZO-1, occludin, E-cadherin and β-catenin 20 . In contrast to the Th2-depdendent induction of leaky claudin-2 observed in intestinal epithelia, neither IL-4 nor IL-13 induced claudin-2 expression in 16HBElo- cells.…”
Section: Models Of Inducible Barrier Dysfunctionmentioning
confidence: 74%
“…Claudin-2, in contrast, is an example of a leaky claudin associated with increased permeability in the intestine, where it is induced by interleukin-13 (IL-13) in a Stat6-dependent manner 19 . Although IL-4 and IL-13 also enhance airway epithelial permeability and barrier dysfunction, they do so without inducing claudin-2 in 16HBE airway epithelial cells 20 . These studies indicate that Th2 cytokine-induced epithelial barrier dysfunction can occur in the intestine and airway by different mechanisms.…”
Section: Apical Junctional Complexes: Basic Structure and Functionmentioning
confidence: 94%
“…Our mouse model was generated by crossing Rac1 fl/fl mice to mice with a Cre recombinase that is expressed in a tetracycline-inducible manner under the control of the promoter for club cell (Clara cell) secretory protein (denoted CCSP-Cre/Rac1 fl/fl mice) (10,14). Disruption of the integrity of the epithelial barrier, such as disruption of apical junctional complexes, is associated with exacerbations of allergic airway inflammation (15,16). We confirmed that a loss of Rac1 expression had no apparent effects on the integrity of the epithelial barrier at baseline: lung morphology, epithelial cell number, tight junction formation, alveolar-capillary membrane integrity, and uptake of antigen in CCSPCre/Rac1 fl/fl mice were all comparable to control animals.…”
mentioning
confidence: 99%
“…Bronchial biopsies and sputum show increased levels of both mRNA expression and protein levels of IL-4, IL-5, IL-13 and their receptors (132). IL-4 and IL-13 has been found to disrupt the human airway epithelial barrier that may contribute to airway inflammation in allergic asthma (143). …”
Section: Th2 Cytokines In Human Asthmamentioning
confidence: 99%